Human CD4 T Cells From Thymus and Cord Blood Are Convertible Into CD8 T Cells by IL-4 - Nunes-Cabaço, Helena; Ramalho-dos-Santos, Andreia; Pires, Ana R.; Martins, Leila R.; Barata, João T.; Sousa, Ana E. (Frontiers in Immunology, 2022)
Commitment to the CD4+ or CD8+ T cell lineages is linked to the acquisition of a functional program broadly defined by helper and cytotoxic properties, respectively. The mechanisms underlying these processes in the human thymus remain largely unclear. Moreover, recent thymic emigrants are thought to have some degree of plasticity, which may be important for the shaping of the immune system and adjustment to specific peripheral needs. We show here that IL-4 induces proliferation-independent de novo synthesis of CD8αβ in human CD4 single-positive (SP) thymocytes, generating a stable CD8SP population that features a diverse TCRαβ repertoire, CD4 expression shut-down and ThPOK downregulation. IL-4 also promotes an innate-like program in both CD4SP and CD8SP thymocytes, characterized by Eomes upregulation in the absence of T-bet, in line with its recognized role in the generation of thymic innate-like CD8+ T cells. The clinical relevance of these findings is further supported by the profile of IL-4 production and IL-4 receptor expression that we identified in the human thymus. Importantly, human cord blood CD4+ T cells preserve the ability to generate Eomes+ CD8+ T cells in the presence of IL-4, with implications in neonatal immunity. Our results support a role for IL-4 in the dynamic regulation of human thymocyte plasticity and identify novel strategies to modulate immune responses.